Analisis Pemanfaatan Abu Sekam Padi dan Tempurung Kelapa untuk Bahan Beton Terhadap Sifat Struktural - Ismi Purnamasari; Kukun Rusyandi; Ida Farida (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
Concrete is a construction material that was widely used in various structural elements of buildings. Concrete formed from a paste made of cement, coarse and fine aggregate mixed with water. Therefore, rice husk ash is an agricultural-based product that can be used as a cement additive without reducing its strength and durability. In this study, a research was conducted on theanalisys of the combined substitution between rice husk ash and coconut shell on the structural properties and composition of concrete. Rice husk ash in normal size can be used for fine aggregate, and coconut shell flakes as coarse aggregate. Variations of concrete mix are 15%, 20% and 25%. As a substitute for concrete, the material was characterized using the modern equipment available, namely X-ray Fluorescence (XRF) and X-ray Diffraction (XRD). The results of XRD and XRF on the two substitution materials showed that the highest concentration was SiO2. Rice husk ash has an SiO2 of 85.65%, while in coconut shell it is 23.79%. Then a method of mixing all the ingredients to be made into concrete was tested mechanically to determine the compressive strength Furthermore, the XRD results of the concrete showed that there were amorphous and crystalline silica phases. The XRF results of the concrete material show that the Silica element is still present in the concrete which indicates it will strengthen the concrete structure. So in this study, rice husk ash and coconut shell ash can be used as a substitute for concrete